Relationship of Arm Strength to Table Tennis Forehand Drive Skills at The PTMSI Club Bengkulu City - Edho Pranata; Tito Parta Wibowo (Universitas Negeri Medan, 2021)
The purpose of this study was to determine whether there is a relationship between arm muscle strength and forehand drive skills in table tennis. This study uses a correlational research method. Subjects or samples in this study were PTMSI athletes in Bengkulu, totaling 20 people.The instruments used in this study were a questionnaire, a questionnaire, as well as an arm muscle strength test instrument and a forehand drive skill test instrument used to collect data. The stages in this study are: (1) Conducting observations, (2) distributing questionnaires and questionnaires, and (3) testing instruments for arm muscle strength and forehand drive skills. As for the value obtained r count 0.65> r table 0.468.Based on the data obtained, it can be concluded that there is a significant relationship between arm muscle strength and forehand drive skills in table tennis.